Becoming a sport, exercise, and performance psychology professional a global perspective - Cremades, J. Gualberto; Tashman, Lauren S. (Lauren Saenz) 1980- (Psychology Press, Taylor & Francis Group, 2014)
This edited book by two prominent professionals of Sport and Exercise and Performance Sciences addresses relevant issues and experiences as one becomes a sport, exercise and performance psychology practitioner. Chapters discuss the supervision and training involved along with models of practice, theory, techniques, and ethical issues.